Perfil clínico e funcional do idoso atendido no Centro Mais Vida do Hospital das Clínicas da Universidade Federal de Minas Gerais, Brasil, 2011 - Marta Aparecida Goulart (2013)
Goals: characterizing the clinical and functional profile of elderly sample in the Centre More Life of Hospital das Clínicas of the Federal University of Minas Gerais, in the period between December 2011 to November 2012. Material and methods: this descriptive cross-sectional study, which sample consisted of 894 elderly people. Variables were analysed by sex, age, education and overall functionality, whereas cognition, mood, mobility and communication. There was also an analysis of the most common diseases and health conditions, the number of medications used and referrals made to the service of Geriatrics of Reference and other medical specialties. Results: among the elderly, 73.4% were female; 18.8% were 60 to 69 years old, 40.5% were between 70 to 79 and 40.6% were 80 years or older. Regarding schooling, 63.5% attended only elementary school. The function more compromised was the vision in 72.65 of the cases; posture with 53.9% of incidence; cognition in 52.1% of the cases; the mood at 51.9% and continence in 50.4%. Diseases and health conditions most frequently identified were hypertension in 74.5% of the attendances, vision disorders in 43.1% and depression in 37.3% of the population of the study. About the referrals made, 45.4% were for the service of Geriatrics of reference. Most of the elderly made use of at least one medicine (44%). It should be noted that there is a lack of uniformity in the completion of plans of healthcare and a high proportion of missing data for the variables. Discussion: the results of the study have the potential to contribute to the improvement of care for the elderly in More Life Centre, in order to identify the main illnesses and diseases. However, emphasized the need for improved information so that more robust inferences can be made about the elderly. Products originated by this dissertation: this work has resulted in two papers submitted to journals.